Inactive Escherichia coli causing perianal abscess - Smita Anand Watwe; Nikunja Kumar Das; Sadhana Chate; Sahjid Mukhida (MRIMS Journal of Health Sciences)
Escherichia coli is a common organism, and its several variants, like inactive, can cause severe human infection, which is difficult to identify in the microbiology laboratory. We present a perianal abscess case report in which we got nonlactose fermenting, nonmotile biochemically inactive bacterial growth. It was not identified by conventional biochemical methods. Final diagnosis of E. coli was done by the automated system and antibiotic treatment was suggested as per the antibiotic susceptibility testing by conventional as well as automated methods. It was found susceptible to amoxicillin–clavulanic acid, piperacillin–tazobactam, and meropenem. The patient was treated with piperacillin–tazobactam combination and get recovered. Inactive E. coli differs from typical E. coli based on motility testing and lactose fermentation. However, other biochemical test results are similar to typical E. coli.